Paul Revere's Ride - Fischer, David Hackett (Oxford University Press, Incorporated, 1994)
One of the foremost American historians offers the first serious look at the events of the night of April 18, 1775--what led up to it, what really happened, and what followed--uncovering a story far more remarkable than the myths of tradition. In Paul Revere's Ride, David Hackett Fischer fashions an exciting narrative that offers deep insight into the outbreak of revolution and the emergence of the American republic. Beginning in the years before the eruption of war, Fischer illuminates the figure of Paul Revere, a man far more complex than the simple artisan and messenger of legend. Indeed, t.